The role of philosophy in the development of education and ethical education - Đặng, Hà Chi; Nguyễn, Anh Tuấn (Đại học Văn hóa Hà Nội, 2020)
Derived from identifying the four roles of philosophy in the development of education, the paper addresses the framework for the "triple fields" of Educational science - Philosophy of education - Education (including the theory of ethical education), in which the philosophy of education in particular; thereby defining the content and structure of educational philosophy based on different scientific approaches. All of these arguments are to support the transformation of the teaching model from "impartial" to "constructive", from "focusing on knowledge" to "focusing more on virtue" and and arousing and training capacity for learners.